1995
DOI: 10.1128/jb.177.17.5161-5165.1995
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of the regulatory nucleotides ppGpp and pppGpp following induction of the stringent response in staphylococci

Abstract: The stringent response in Escherichia coli and many other organisms is regulated by the nucleotides ppGpp and pppGpp. We show here for the first time that at least six staphylococcal species also synthesize ppGpp and pppGpp upon induction of the stringent response by mupirocin. Spots corresponding to ppGpp and pppGpp on thin-layer chromatograms suggest that pppGpp is the principal regulatory nucleotide synthesized by staphylococci in response to mupirocin, rather than ppGpp as in E. coli.Bacteria adapt to amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
50
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 31 publications
4
50
1
Order By: Relevance
“…In amino acid-starved E. coli cells, the pppGpp/ppGpp ratio is generally smaller than 1 but varies widely depending on the nature of the spoT or gpp alleles (reviewed in reference 3). In similarly starved S. equisimilis cells, we find a pppGpp/ppGpp ratio of Յ0.1, in contrast to the relative quantities of the two nucleotides in Bacillus subtilis (14) and Staphylococcus aureus (6), where pppGpp has been reported to be the more abundant nucleotide during amino acid starvation. Tetracycline efficiently blocks the net accumulation of (p)ppGpp (Fig.…”
Section: Discussioncontrasting
confidence: 47%
“…In amino acid-starved E. coli cells, the pppGpp/ppGpp ratio is generally smaller than 1 but varies widely depending on the nature of the spoT or gpp alleles (reviewed in reference 3). In similarly starved S. equisimilis cells, we find a pppGpp/ppGpp ratio of Յ0.1, in contrast to the relative quantities of the two nucleotides in Bacillus subtilis (14) and Staphylococcus aureus (6), where pppGpp has been reported to be the more abundant nucleotide during amino acid starvation. Tetracycline efficiently blocks the net accumulation of (p)ppGpp (Fig.…”
Section: Discussioncontrasting
confidence: 47%
“…Comparison of the global expression profile of heme-exposed S. aureus ⌬hrtA with the global expression profile of S. aureus upon cold shock, heat shock, SOS induction, stringent response induction, acid shock, alkaline shock, Mn 2ϩ starvation, or Zn 2ϩ starvation indicated that the stringent response most closely resembles the heme response of S. aureus ⌬hrtA (37.4% similarity) ( Table 2) (1, 7). The bacterial stringent response is induced under carbon or amino acid insufficiency through ribosome stalling, which leads to an increase in the intracellular concentration of (p)ppGpp (6). This occurs through the induction of the stringent response regulatory factor RelA (SACOL1689), the transcript of which is up-regulated upon treatment of S. aureus with the stringent response-inducing antimicrobial agent mupirocin and is increased 9.2-fold in S. aureus ⌬hrtA exposed to heme (see Table S1 in the supplemental material) (1).…”
Section: Resultsmentioning
confidence: 99%
“…Mupirocin is an antimicrobial agent that induces the staphylococcal stringent response by inhibiting isoleucyl tRNA synthetase, thereby increasing the cellular concentration of uncharged tRNA Ile molecules (8,11). Using realtime PCR, we determined that 30 min of mupirocin treatment (60 g ml Ϫ1 ) increased the transcript titers of the stringent response control factor relA and the ilv operon (3-and Ͼ1,000-fold, respectively), whereas rpsL transcript levels were decreased (5-fold); cell viability was marginally affected (data not shown).…”
Section: Resultsmentioning
confidence: 99%